Lawyers and the public good democracy in action? - Paterson, Alan (Cambridge, UK New York Cambridge University Press, 2012)
Chiefly covers Great Britain, but also includes some discussion of several other common law jurisdictions.
Includes bibliographical references (p. 198-211) and index.
Keywords: Public interest law -- Great Britain; Lawyers -- Great Britain; Judges -- Great Britain; Justice, Administration of -- Great Britain; Democracy -- Great Britain